Entry of the Slovak Army into the War Against the Soviet Union in 1941 - Igor Baka; Matej Medvecký (Review (Institute of National Remembrance))
While preparing the Operation Barbarossa the Nazi Germany did not originally consider participation of other countries apart from Romania and Finland that had territorial demands against Soviet Union. German military planners considered for some time the possibility to appoint two Slovak infantry divisions with security tasks in the rear, and in May 1941 there were voices calling for the utilization of two Slovak divisions to enforce the 17th Army of the Army Group South even despite open distrust of Adolf Hitler towards Slavs. Since the preparations were taking place on the Slovak territory as well, Slovak Minister of Defence Gen. Ferdinand Čatloš, in a conversation with German military attaché, Lt. Col. Heinrich Becker, stated that in case of Hungarian participation Slovakia would like to take part in the campaign as well. Germans, at first, pointed out an overall unreadiness of the Slovak Armed Forces but finally – only shortly before June 22nd, 1941 – Hitler declared his wish that the “Slovak Army attended some prospective action”. With the goal to show more loyalty than Hungarians, Slovak politicians and especially the Prime Minister Vojtech Tuka acted proactively without waiting for the Germans to specify their requirements. The paper analyses the circumstances of Slovak entry into the war against the Soviet Union in the summer of 1941, and summarizes the latest findings of Slovak historiography.